Plasma levels of mannan‐binding lectin (MBL)‐associated serine proteases (MASPs) and MBL‐associated protein in cardio‐ and cerebrovascular diseases. (6th June 2013) - Frauenknecht, V.; Thiel, S.; Storm, L.; Meier, N.; Arnold, M.; Schmid, J.‐P.; Saner, H.; Schroeder, V.
Summary Growing evidence suggests a prominent role of the complement system in the pathogenesis of cardio‐ and cerebrovascular diseases (CVD). Mannan‐binding lectin‐associated serine proteases (MASPs) MASP‐1 and MASP‐2 of the complement lectin pathway contribute to clot formation and may represent an important link between inflammation and thrombosis. MBL‐associated protein MAp44 has shown cardioprotective effects in murine models. However, MAp44 has never been measured in patients with CVD and data on MASP levels in CVD are scarce. Our aim was to investigate for the first time plasma levels of MAp44 and MASP‐1, ‐2, ‐3 concomitantly in patients with CVD. We performed a pilot study in 50 healthy volunteers, in stable coronary artery disease (CAD) patients with one‐vessel (n = 51) or three‐vessel disease (n = 53) and age‐matched controls with normal coronary arteries (n = 53), 49 patients after myocardial infarction (MI) and 66 patients with acute ischaemic stroke. We measured MAp44 and MASP‐1 levels by in‐house time‐resolved immunofluorometric assays. MASP‐2 and MASP‐3 levels were measured using commercial enzyme‐linked immunosorbent assay kits. MASP‐1 levels were highest in subacute MI patients and lowest in acute stroke patients. MASP‐2 levels were lower in MI and stroke patients compared with controls and CAD patients. MASP‐3 and MAp44 levels did not differ between groups. MASP or MAp44 levels were not associated with severity of disease. MASP and MAp44 levels were associated with cardiovascular risk factors including dyslipidaemia, obesity and hypertension. Our results suggest that MASP levels may be altered in vascular diseases. Larger studies are needed to confirm our results and elucidate the underlying mechanisms.